2020
DOI: 10.3390/life10100229
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing and Comparative Genome Analysis of the Halotolerant Deep Sea Black Yeast Hortaea werneckii

Abstract: Hortaea werneckii, an extreme halotolerant black yeast in the order of Capnodiales, was recently isolated from different stations and depths in the Mediterranean Sea, where it was shown to be the dominant fungal species. In order to explore the genome characteristics of these Mediterranean isolates, we carried out a de-novo sequencing of the genome of one strain isolated at a depth of 3400 m (MC873) and a re-sequencing of one strain taken from a depth of 2500 m (MC848), whose genome was previously sequenced bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…The potential of some fungi for their phenotypic and genetic adaptation in response to extreme habitat and climate change has been acknowledged here. Several fungi have characterized themselves to adapt in environments with low water activity and high concentrations of toxic ions by complex molecular and cellular adaptation (Gostinèar et al, 2011;Gladfelter et al, 2019;Romeo et al, 2020). Spores of some marine fungi have developed strategies of sheath and appendages to attach, float, and adapt to a new environment.…”
Section: Adaptation Of Marine Fungi To Climate Changementioning
confidence: 99%
See 3 more Smart Citations
“…The potential of some fungi for their phenotypic and genetic adaptation in response to extreme habitat and climate change has been acknowledged here. Several fungi have characterized themselves to adapt in environments with low water activity and high concentrations of toxic ions by complex molecular and cellular adaptation (Gostinèar et al, 2011;Gladfelter et al, 2019;Romeo et al, 2020). Spores of some marine fungi have developed strategies of sheath and appendages to attach, float, and adapt to a new environment.…”
Section: Adaptation Of Marine Fungi To Climate Changementioning
confidence: 99%
“…These adaptation mechanisms and their effects are highly dependent on different levels of biological organization and follow a cascade of events (molecular and cellular, whole organisms, population, and community). Fungi isolated from hypersaline marine environments, deepsea hydrothermal vents, and deep-sea sediments have different molecular and cellular mechanisms for adaptation, e.g., gene expression, high osmolarity glycerol (HOG) signaling pathway, melanization of the cell wall, composition and accumulation of ions, enzymes involved in fatty acid modifications, and plasma membrane composition (Turk and Plemenitaš, 2002;Kogej et al, 2006;Romeo et al, 2020). Fungi with these characters have been described for genera such as Aspergillus, Cladosporium, Emericella, Eurotium, Hortaea, Trimmatostroma, and Wallemia.…”
Section: Adaptation Of Marine Fungi To Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…In deep-sea hypersaline basins (salinity between 70 and 172 ppt) located in the Eastern Mediterranean Sea that harbored Ascomycota and Basidiomycota [ 85 ], a metatranscriptomic analysis revealed that the majority of the detected rRNA signatures were related to the genera Aspergillus and Penicillium [ 33 ]. The genus Hortaea is commonly detected from deep-sea environments [ 22 , 60 , 61 , 66 , 83 , 86 , 87 ], specifically the species H. werneckii , a black yeast that has been classified as halotolerant in Mediterranean deep-sea waters [ 88 ] and as halophilic in deep-sea hydrothermal vents [ 83 ]. Marine-derived Penicillium and Aspergillus species are an excellent and widely used source for many useful bioactive secondary metabolites [ 89 , 90 ].…”
Section: Out Of the Dark: The Hidden Mycota Of The Deep Sea And Thmentioning
confidence: 99%